Factors Influencing the Willingness to Use E-Banking: A Study of Management Students in Pokhara, Nepal (Journal of Nepalese Business Studies, 2025)
This study explores the factors that influence management students’ intention to use online banking services in Pokhara, Nepal. Drawing on the Technology Acceptance Model (TAM), it examines the impact of perceived usefulness (PU), e-service quality (ESQ), and perceived ease of use (PEOU) on students’ behavioral intention to adopt online banking. Data were collected from 155 students through a structured questionnaire, and the analysis employed descriptive statistics, correlation analysis, and multiple regression techniques. The results indicate that PU and PEOU significantly predict behavioral intention, whereas ESQ does not show a significant effect, suggesting that service quality functions as a basic expectation rather than a motivating factor for this technologically proficient group. The findings imply that Nepalese banks should focus their marketing efforts on highlighting the advantages and user-friendliness of e-banking platforms while consistently maintaining acceptable service quality standards. The study confirms the relevance of the TAM framework in the Nepalese context and enhances understanding of the role of ESQ in e-banking adoption. Students expressed highly positive perceptions across all measured dimensions, and the results contribute valuable insights into the usefulness of e-banking among business students and the key factors driving its continued use in routine banking activities.